2021
DOI: 10.3390/insects12080716
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Pesticides and Electromagnetic-Fields on Honeybees: Multi-Stress Exposure

Abstract: Honeybee and general pollinator decline is extensively reported in many countries, adding new concern to the general biodiversity loss. Many studies were addressed to assess the causes of pollinator decline, concluding that in most cases multi-stress effects were the most probable ones. In this research, the combined effects of two possible stress sources for bees, pesticides and electromagnetic fields (multi-stress conditions), were analyzed in the field. Three experimental sites were chosen: a control one fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 112 publications
0
4
0
1
Order By: Relevance
“…Keywords clusters "honeybee", "animals", "Apis mellifera", "apoideos" are mostly related to the number of studies that were published in the past 12 years (2010-2022), because there is special interest on preserving bees and because of major efforts to understand the cause of beesʼ behavior 84 .…”
Section: Discussionmentioning
confidence: 99%
“…Keywords clusters "honeybee", "animals", "Apis mellifera", "apoideos" are mostly related to the number of studies that were published in the past 12 years (2010-2022), because there is special interest on preserving bees and because of major efforts to understand the cause of beesʼ behavior 84 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, field investigations (Lupi et al 2020(Lupi et al , 2021 have shown negative effects of electric and magnetic fields from power lines in combination with pesticides on various biomarkers of bee health, separately as well as in combination. The strongest negative effects on vital parameters were observed in combined multistress situations.…”
Section: Biological Effectsmentioning
confidence: 99%
“…From the study by Wyszkowska et al (2019), it is evident that upon exposure of honey bees (A. mellifera carnica F.) to 50 Hz ELF-EMF at 1mT and 7mT, induced a negative influence on the foraging and migratory behaviour of the bees. Thus, ELF-EMF can be accounted as a biological stressor affecting their orientation and motor skills, finally reducing the capability of crop pollination (Lupi et al, 2021).…”
Section: Emf's Impact On Foragingmentioning
confidence: 99%